RESEARCH ON THE RELATIONSHIP BETWEEN THE SEVERITY OF THE COURSE OF PSORIASIS AND METABOLIC SYNDROME AND THE LEVEL OF INDICATORS OF SYSTEMIC INFLAMMATION - Yemchenko, Y.O.; Kaydashev, I.P.; Ishcheykin, K.Ye.; Bezeha, O.V. (World of Medicine and Biology, 2023)
In patients with moderate psoriasis with concomitant metabolic syndrome, the indicators of general clinical and biochemical blood tests and carbohydrate and lipid metabolism were determined, and indicators of systemic inflammation were assessed by the level of susceptible C-reactive protein, ceruloplasmin, interleukin-6 and tumor necrosis factor-α. A laboratory study found that in patients with moderate psoriasis with concomitant metabolic syndrome, an important role is played by the systemic inflammatory process, which is accompanied by the development of insulin resistance, impaired lipid and nitrogen metabolism, and regulation of vascular tone. Furthermore, an increase in the intensity of systemic inflammation is accompanied by an increase in skin lesions, an increase in systolic blood pressure, and a violation of lipid and carbohydrate metabolism.
Keywords: psoriasis; metabolic syndrome; systemic inflammation; dyslipidemia; insulin resistance